School-based comprehensive sexuality education for prevention of adolescent pregnancy: a scoping review - Su Mon Myat; Porjai Pattanittum; Jen Sothornwit; Chetta Ngamjarus; Siwanon Rattanakanokchai; Kyaw Lwin Show; Nampet Jampathong; Pisake Lumbiganon (BMC, 2024)
Abstract Background Adolescent pregnancy is a global public health problem. Numerous approaches for Comprehensive Sexuality Education (CSE) delivery in schools have been implemented around the world. Previous reviews on CSE did not follow the International Technical Guidance on Sexuality Education (ITGSE) because CSE is very diverse in terms of population, interventions, settings and outcomes. We conducted this scoping review to identify and map the evidence of school-based CSE for prevention of adolescent pregnancy with emphasis on adolescents' contraceptive use, unintended pregnancy and abortion. Methods We searched PubMed, CENTRAL, Scopus, ISI Web of Science, CINAHL, and WHO ICTRP to identify potential eligible studies from their inception to 4th Nov 2023.We included randomized controlled trials (RCTs) and non-RCTs of CSE implemented in public or private schools for adolescents. CSE was defined as a multi-session intervention in school that covered topics including contraception, pregnancy, abortion, and HIV/STI. School-based interventions were the main intervention that may be either stand-alone or multicomponent. There was no limitation on study's geographical area, but only English-language studies were considered. Two reviewers selected and extracted data independently, discussed for consensus or consulted the third reviewer if there were discrepancies for final conclusion. Data were presented using figures, map and table. Results Out of 5897 records, 79 studies (101 reports) were included in this review. Most studies were conducted in the United States and other high-income countries in secondary or high schools with cluster RCTs. All studies included participatory methods. Almost all studies included Sexual and Reproductive Health which is the eighth concept of CSE. Very few studies reported the prespecified primary outcomes of contraceptive use during last sex, unintended pregnancy and abortion and hence this highlighted the gaps of available evidence for these outcomes. The number of concepts, components, duration and providers of CSE varied across the included studies. However, none of the interventions identified in this scoping review adhered to the ITGSE recommended approach. Conclusions Our scoping review shows gaps in school-based CSE implementation in terms of completeness of concepts, components, providers, duration and outcomes recommended by ITGSE.